Quantitative risk assessment for the transport of ammonia by rail - Che Hassan, Che Rosmani; Puvaneswaran, B.; Abdul Raman, Abdul Aziz; Mahmood, Noor Zalina; Hung, F.C.; Sulaiman, N.M. (Wiley, 2010)
Risk assessments are considered to be an essential tool in ensuring the safety of engineering projects. The benefits of using risks assessments have prompted its acceptance in the safety legislation for a number of industries. The use of quantitative risk assessment for rail transportation of hazardous materials has gained more attention in recent years, because the amount Of the transported hazardous materials is large, and the transportation route often passes through populated areas, such as cities. in this study, the risk for the ammonia transportation by rail in Malaysia was conducted by combining the results from a previous failure frequency analysis and consequence analysis. The assessment results acknowledged the significant effects of train speeds on the overall individual risk. The risk with a tolerable risk limit of 1 X 10(-6) per year increased significantly with more train accidents occurring at increasing speeds. Most of the surrounding populations along the transportation route analyzed are exposed to higher risk levels than the tolerable limit. This risk exposure to the public demonstrates the need for proper planning of moving ammonia through populated areas. (C) 2009 American Institute of Chemical Engineers Process Saf Prog 29: 60-63, 2010